Emerging treatments in the management of psoriasis: biological targeting with ustekinumab - Marina Papoutsaki; Antonio Costanzo; Sergio Chimenti (Dove Medical Press, 2009)
Marina Papoutsaki, Antonio Costanzo, Sergio ChimentiDepartment of Dermatology, University of Rome, “Tor vergata”, Rome, ItalyAbstract: Psoriasis is a chronic, genetically determined, immune-mediated, inflammatory skin disease affecting approximately 2% to 3% of Caucasian population. Given the well-established role of the immuno-mediated inflammation in the pathogenesis of psoriasis, in the past few years several key steps in the pathogenesis of this disease have been elucidated and the increased knowledge led to the development of specific drugs, commonly defined as “biologics” targeting one or more of these steps. At present an anti-CD11a antibody (efalizumab), an anti-LFA3/CD2 receptor (alefacept) and 3 antitumor necrosis factor alpha agents (adalimumab, etanercept, infliximab) are now commercially available for the treatment of both psoriasis and psoriatic arthritis. Recent studies have demonstrated that interleukins (IL) 12 and 23 play an important role in the pathophysiology of psoriasis. In fact members of the IL-12 family of cytokines have the potential to act as the next major cytokine(s) in pathogenesis and the treatment of psoriasis. Ustekinumab (CNTO 1275, Centocor Inc, Malvern, PA, USA) is a human monoclonal antibody that binds to the shared p40 protein subunit of human interleukins 12 and 23 with high affinity and specificity, thereby preventing interaction with their surface IL-12Rβ1 receptor. Different clinical studies have been conducted to date. In particular a phase II study and two phase III studies, PHOENIX 1 together with PHOENIX 2, show very encouraging results. This review reports on the latest progress made in the clinical use of biologic drugs for psoriasis focusing on the new human IL-12/23 monoclonal antibody, ustekinumab, for psoriasis.Keywords: psoriasis, ustekinumab, interleukin-12/23 monoclonal antibody